Fighting corruption with social accountability: a comparative analysis of social accountability mechanisms' potential to reduce corruption in public administration - Schatz, Florian (2013)
Given the poor track record of traditional anti-corruption initiatives, donors and governments are increasingly looking at how civil society can fight corruption in public administration. Social accountability mechanisms intend to perform this role by holding officials directly accountable through citizen engagement. However, this article argues that social accountability mechanisms are only capable of reducing corruption systemically if they activate horizontal accountability and sustain it through the sanctioning mechanisms of electoral accountability. A comparative case study analysis using the cases of the Ugandan Public Expenditure Tracking Survey and the Bangalore Citizen Report Card is applied to test this hypothesis. The Tanzanian Public Expenditure Tracking Survey and an example of citizen engagement in Mumbai are employed as shadow cases to provide additional evidence for the hypothesis. The results indicate that social accountability mechanisms must be inclusive, broad, with public effect and embedded in other accountability relationships to fight corruption effectively. Electoral accountability is key, and support to social accountability mechanisms should therefore always be well placed within a broader agenda aimed at strengthening democratic governance. - Reproduced.
Keywords: Citizen participation; Public sector accountability; Public administration; Corruption; Social accountability